2023
DOI: 10.3390/microorganisms11010196
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Novel Bacterial Strains Pseudomonas extremaustralis CSW01 and Stutzerimonas stutzeri CSW02 from Sewage Sludge for Paracetamol Biodegradation

Abstract: Paracetamol is one of the most used pharmaceuticals worldwide, but due to its widespread use it is detected in various environmental matrices, such as surface and ground waters, sediments, soils or even plants, where it is introduced mainly from the discharge of wastewater and the use of sewage sludge as fertilizer in agriculture. Its accumulation in certain organisms can induce reproductive, neurotoxic or endocrine disorders, being therefore considered an emerging pollutant. This study reports on the isolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Similarly, Bacillus altitudinis has been reported to generate carbonate minerals in mangroves and manganese-contaminated environments [48,49]. In contrast, this is only the second report in the literature on the urease-producing ability of Bacillus aryabhattai and its suitability for MICP [50]. One bacterial isolate was identified as Stutzerimonas stutzeri (S1S19) belonging to the genus Stutzerimonas, a recently defined genus that was previously classified as part of the genus Pseudomonas [51].…”
Section: Resultsmentioning
confidence: 88%
“…Similarly, Bacillus altitudinis has been reported to generate carbonate minerals in mangroves and manganese-contaminated environments [48,49]. In contrast, this is only the second report in the literature on the urease-producing ability of Bacillus aryabhattai and its suitability for MICP [50]. One bacterial isolate was identified as Stutzerimonas stutzeri (S1S19) belonging to the genus Stutzerimonas, a recently defined genus that was previously classified as part of the genus Pseudomonas [51].…”
Section: Resultsmentioning
confidence: 88%
“…Paracetamol in the environment can cause genotoxicity, hepatotoxicity, endocrine interference, and other negative effects on organisms. A study found the Pseudomonas stutzeri and Pseudomonas extremaustralis were able to degrade very high concentrations of paracetamol in solution as a sole carbon and energy source [13]. Phylogenetic analysis based on the phylogeny of the core genome of the Pseudomonadaceae family and several indices based on shared genes of members of new genera, as well as their phenotypic characteristics, including denitrification characteristics and lack of arginine dihydrogenase activity, support the proposal of the genera.…”
Section: Discussionmentioning
confidence: 86%
“…In recent years, an MDR plasmid co-harboring the carbapenem resistance gene bla (VIM-2) and tigecycline resistance gene cluster tmexCD1-toprJ1 was identified in a Pseudomonas stutzeri isolate [11,12]. A Stutzerimonas stutzeri strain isolated from sewage sludge produced in wastewater treatment plants could degrade very high paracetamol concentrations in solutions wherein paracetamol was the sole carbon and energy source, and none of the Stutzerimonas stutzeri strains were previously described as paracetamol degraders [13]. Pseudomonas stutzeri, which can inhibit corrosion by sulfate-reducing bacteria, was isolated from the soil in an enrichment culture [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, 17 bacterial strains were isolated from the sewage of a Wastewater Treatment Plant (WWTP) in Seville (Spain), but only two of them ( Pseudomonas stutzeri CSW02 and Pseudomonas extremoustralis CSW01) biodegraded high concentrations of PAR as sole carbon and energy source. The process reached 100% degradation at 500 mg L −1 PAR, 150 rpm, and 30°C for 6 h, showing the high efficiency of these strains ( Table 2 , entry 33 and 34, respectively; Vargas-Ordóñez et al, 2023 ).…”
Section: Biodegradation Of Paracetamolmentioning
confidence: 97%
“…Due to its large-scale use, this drug can be found in different environments, especially in water bodies. Regarding this, it is noteworthy that PAR is bioaccumulative in aquatic organisms and may induce reproductive and neurotoxic disorders ( Vargas-Ordóñez et al, 2023 ). Therefore, this compound was considered an emerging pollutant that requires environmentally safe strategies for its removal.…”
Section: Biodegradation Of Paracetamolmentioning
confidence: 99%